Analysis of Rice Market Potential in Phnom Penh, Cambodia - Sros, Em; Mardy, Serey; Chanthuch, Try (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Phnom Penh is Cambodia's capital and biggest city, making it an important market for rice, the country's main food. To understand the market possibilities for rice in Phnom Penh, you need to look at what customers want, how the market works, who the competitors are, and where there are chances to grow and innovate. This study paper looks at the potential of the rice market in Phnom Penh, Cambodia. This study will propose ways to enhance rice output policies in Cambodia. The research shows that the rice market in Phnom Penh has a lot of room to grow in the future. The high demand, steady supply, opportunities for exporting, new ideas, and government support make this business important for the city's economic growth. To reach its full potential, the sector must continue to adapt to new challenges and use innovative and sustainable approaches. The future of the rice market in Phnom Penh looks promising and will bring significant economic benefits to the city. Cambodia has a strong foundation for rice farming because of its fertile land, experienced farmers, and growing research and development activities. The country is good at selling products to other countries, especially close ones. It's important to enhance product quality, meet international standards, and make the supply line more efficient. The industry is facing big challenges like climate change, changing prices, competition from other countries growing rice, and the need for improved facilities and market access. To enhance Cambodia's rice markets as well as improving productivity, make it easier to access markets, and increase support from policies. This will help provide enough food, improve life in rural areas, and grow the economy.